ANALISIS GELOMBANG PRIMER (P) DAN SEKUNDER VERTIKAL (SV) DALAM MODEL SEISMIK BIAS (Analysis of the Primary (P) and the Vertical Secondary (SV) Waves in a Seismic Refracted Model) - Perpustakaan UGM, i-lib ([Yogyakarta] : SekolahPascasarjana Universitas GadjahMada, 2000)
ABSTRACT This research presented a two dimension seismic model with homogeneous isotropic layered media, which consisted of Plexiglas and Aluminum. The purpose of this research was to determine the velocities of P and SV waves, the thickness of Plexiglas, the elastic constants of Plexiglas and Aluminum, and the dominant frequency of recorded signal. This experiment used a pair of piezoelectric crystals with dominant frequency of 100 kHz. A pulse generator, a band pass filter, and an amplifier had been constructed to complete the experiment. A digital oscilloscope was used for the data recording. Then the data were processed by using SPSS and PITSA programs. The results showed that, the accuracy of the P and the SV waves velocity in Plexiglas and Aluminum was 96.5% - 99.4%. The accuracy of the thickness of the Plexiglas was 97.7% - 98%. The elastic constants of the Plexiglas, i.e., the shear modulus, Lame constant, Poisson's ratio, Young's modulus and bulk modulus had an accuracy of 93.5% - 99%, whereas of the Aluminum had an accuracy of 94% - 99%. From the spectral analysis of the recorded signal, the dominant frequency of the signal was between 80 kHz and 100 kHz.